REAKTUALISASI PROGRAM RUMAH PANGAN LESTARI BERTUJUAN MENCIPTAKAN KEBERLANJUTAN DAN KETAHANAN PANGAN DI TINGKAT RUMAH TANGGA - Cisyara, Sinta Naila; Novyantari, Zahrani Tri; Khotimah, Iin Husnul; Karwati, Lilis (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The Sustainable Food Home Area (KRPL) is a form of optimizing the use of yards which is carried out through efforts to empower women to optimize their yards so that they can experience the benefits of yards as a source of family food. With this, an area can be created that is rich in sources of food needs that can be produced by every woman in the household from the results of optimizing the yard. The approach taken in this program is carried out through the development of sustainable agriculture, by establishing a nursery from a small area of ​​land by prioritizing local resources so as to maintain sustainability. In Indonesia itself, there is quite a large yard area, reaching 10.3 Ha or around 14% of the entire agricultural area. To overcome this, the government issued a policy in regulation Number 17 of 2015 concerning Food Security and Nutrition in Article 26 which states that one of the efforts to diversify food is through the use of yard land. The importance of the government in creating food diversity in meeting community needs in accordance with local potential to create a prosperous community life. Therefore, currently many village governments are holding KRPL implementation programs in their areas.